Coletivo Cê: processos e percursos de redesterritorialização: aprendendo com a experiência - Almeida, Hércules Soares de (2017)
The framework presented here proposes to share a cartography of the processes and paths of the deterritorialization and reterritorialization of Coletivo Cê. It is also a scratch to the surface about the knowledge of experience and ethical, aesthetic and political movements in research about education. We will present ways that allowed a research carried out from the perspective of implication, requiring a vibrating body and implied in the research. The author of this research has been working on the Coletivo Cê for more than seven years. The Coletivo Cê is a group of artists who research the language of theater, in the city of Votorantim, São Paulo. This research goal was to trace the processes and routes from the year of its foundation in 2009 to the present day. Within this proposal, there was also a close look at the concepts of authors who lead and compose the living and pulsating picture of cartography, such as Gilles Deleuze, Félix Guattari, Suely Rolnik, Jacques Ranciére, Jorge Larrosa Bondía, Paulo Freire, sociologist Boaventura de Souza Santos and others who believe in the work of thought as a vibrating space of our urgencies. An intellectual production in the field of Education, proposing cartography as an aesthetic possibility for the urgencies that plague us, able to understand the "educate" mediated by artistic actions of cultural collectives groups, which can become a practice of social transformation for the emancipation of people.